(untitled) (Revista Cocar, 2023)
O presente artigo trata de um relato de experiência e o objetivo é descrever as práticas educacionais vivenciadas na ação de extensão intitulada “De volta às Origens III”. A ação de educação popular para inclusão social de comunidades do interior do munícipio do Acará foi promovida pela Universidade do Estado do Pará em conjunto com o Núcleo de Ensino e Extensão. A ação foi pautada em uma perspectiva freiriana e descrita a partir de três eixos: roda de conversa saúde da mulher; trilhas ecológicas; oficina sobre Libras. A metodologia foi participativa, promovendo-se interação com e entre o público e constatando-se uma maior dialogia dos partícipes com seus saberes culturais, suas opiniões e suas práticas sociais. Palavras-chave: Educação popular; Extensão; Práticas pedagógicas. Abstract This article deals with an experience report and the objective is to describe the educational practices experienced in the extension action entitled “Back to the origins III”. The popular education action for the social inclusion of communities in the interior of the municipality of Acará was promoted by the University of the State of Pará in conjunction with the Education and Extension Center. The action was based on a Freirean perspective and described from three axes: women’s health conversation wheel; ecological trails; workshop on Libras. The methodology was participative, promoting interaction with and among the public and verifying a greater dialog between of the of the participants with their cultural knowledge, their opinions and their social practices. Keywords: Popular education; Extension; Pedagogical practices. Key-words: Popular education; Extension; Pedagogical practices.